Pendidikan Seumur Hidup dan Implikasinya - Jannah, Fathul (Dinamika Ilmu: Jurnal Pendidikan, 2013)
Long life education is a process of continuous education lasts indefinitely and the place. that starts from birth to the end of life. That is that occurred in the family, at school, at work and in public life. Long life educational purposes is to develop the potential of the human personality in accordance with the nature and essence, develop awarnes that the growth anddevelopment of the human personality is vibrant and dynamic, expands and increases hope and human life. The implications long life education programs can be grouped into several categories: functional literacy education, vocational education, professional education, education in the direction of change and development and civic education and politicalmaturity.